UJI KINERJA PROTOTYPE KOMPOR BIOBRIKET DITINJAU DARI VARIASI KETINGGIAN ALAS RUANG BAKAR DAN PEMANFAATAN PANAS BUANGAN MENGGUNAKAN THERMOELECTRIC GENERATOR - Arif Zakiatul Fikri; Anisa Rahmawati; Agus Manggala; Zurohaina; Jaksen (KINETIKA, 2022)
Biobriquette stove is one type of stove that can be developed as a renewable energy source. This biobriquette stove is also one of the best solutions in improving the briquette combustion system so far which is still less desirable and the treatment is still traditional. The prototype of this biobriquette stove was carried out to test the performance using the hot start water boiling test (WBT) method. In this study, primary air is supplied by a blower with a speed of 6.8 m/s, and the use of heat from the combustion chamber which can be converted into electrical energy by a thermoelectric generator component with the largest voltage obtained is 10 Volts. Performance testing of this biobriquette stove prototype refers to SNI 7926:2013, this prototype is included in the medium size stove category because it has a maximum capacity of 3 kg with an operating time of 2 ours 58 minutes. The best thermal efficiency obtained is 28,27% with a specific fuel consumption (Sc) of 0.61 kg/h, the greater the efficiency value, the smaller the fuel consumption, and for the best combustion efficiency, the value is 0.9927.